Selective addressing of solid-state spins at the nanoscale via magnetic resonance frequency encoding - H. Zhang (Nature Portfolio, 2017)
Selective nanoscale addressing of solid-state spins Arrays of spins in solids are a promising modality for a wide range of quantum science applications—from sensing to information processing. A team led by Ronald Walsworth at Harvard University adapted methods from magnetic resonance imaging (MRI) to realize site-selective addressing and coherent control of small arrays of optically active electronic spins in diamond known as nitrogen vacancy (NV) colour centres. Microcoils fabricated on the diamond chip provide electrically tunable magnetic field gradients that allow selective NV spin addressing with 30 nm resolution. The team experimentally demonstrated site-selective NV electron spin resonance spectroscopy, Rabi oscillations, Fourier magnetic imaging, and nuclear magnetic resonance (NMR) spectroscopy. The approach should be scalable to selective coherent control of large-scale arrays of strongly interacting NVs, with a broad spectrum of high-impact quantum science applications.